The registration of point cloud data from range imaging camera - Altuntas, Cihan; Yildiz, Ferruh (Geodesy and Cartography, 2013)
The measurement and 3D modelling techniques have been evolved as parallel technological improvements. Every new technique provides an opportunity for low-cost and fast measurements. The latest method for 3D measurement is the range imaging (RIM) camera. The new period in photogrammetry and 3D modelling applications has begun with the RIM cameras, and it has brought new research areas for scientists. The measurement capabilities, accuracies and application areas of RIM cameras have been increased by the time. In this study, the registration of point cloud data of RIM camera was investigated to perform 3D modelling task.